2018
DOI: 10.1523/jneurosci.0436-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

A Generic Mechanism for Perceptual Organization in the Parietal Cortex

Abstract: Our visual system's ability to group visual elements into meaningful entities and to separate them from others is referred to as scene segmentation. Visual motion often provides a powerful cue for this process as parallax or coherence can inform the visual system about scene or object structure. Here we tested the hypothesis that scene segmentation by motion cues relies on a common neural substrate in the parietal cortex. We used fMRI and a set of three entirely distinct motion stimuli to examine scene segment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 83 publications
5
30
0
Order By: Relevance
“…This explanation seems unlikely because an inverse V1-LOC relationship has also been established for non-ambiguous shape-like stimuli vs unstructured displays (Murray et al, 2002). Moreover, at least broadly in line with our results, recent studies (Grassi et al, 2016, 2018) found no evidence for the involvement of the LOC when a dynamic, bistable global-local stimulus constantly triggered shape-based interpretations (i.e., moving disks forming large squares or small circles).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This explanation seems unlikely because an inverse V1-LOC relationship has also been established for non-ambiguous shape-like stimuli vs unstructured displays (Murray et al, 2002). Moreover, at least broadly in line with our results, recent studies (Grassi et al, 2016, 2018) found no evidence for the involvement of the LOC when a dynamic, bistable global-local stimulus constantly triggered shape-based interpretations (i.e., moving disks forming large squares or small circles).…”
Section: Discussionsupporting
confidence: 91%
“…These conditions echoed the global-local aspects of the diamond stimulus without varying in shape information. We hypothesized that if the between-area response amplitude mechanism between lower visual cortex and VLOC/LOC we and others observed (Fang et al, 2008; Grassi et al, 2018; Murray et al, 2002) indeed mediates global object perception per se, we should be able to conceptually replicate this relationship.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Previous work suggests that visual motion often provides powerful cues for scene segmentation for both human and artificial systems (Wagemans et al, 2012;Shi & Malik, 1998). More recently, an fMRI study finds that when showing a class of bistable moving stimuli, the perceptual scene-segmentation was associated with an increased activity in the posterior parietal cortex (PPC) together with a decreased neural signal in the early visual cortex (Grassi, Zaretskaya, & Bartels, 2018). This suggests that PPC is a hub involved in structuring visual scenes based on different motion cues.…”
Section: Implications In Neuroscience Computer Vision and Graphicsmentioning
confidence: 99%